2015
DOI: 10.3892/or.2015.4000
|View full text |Cite
|
Sign up to set email alerts
|

Ligularia fischeri inhibits endothelial cell proliferation, invasion and tube formation through the inactivation of mitogenic signaling pathways and regulation of vascular endothelial cadherin distribution and matrix metalloproteinase expression

Abstract: Abstract. Ligularia fischeri (LF) has been used as an edible herb and traditional medicine for the treatment of inflammatory and infectious diseases. In the present study, we report the effects and molecular mechanism of the ethanolic extract of LF on cell proliferation, invasion and tube formation in human umbilical vein endothelial cells (HUVECs). LF-mediated inhibition of cell proliferation was accompanied by reduced expression of cell cycle-related proteins such as cyclin-dependent kinases (Cdks) and cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
(65 reference statements)
0
8
0
2
Order By: Relevance
“…As a nonmedicinal alternative, MCE has been found to be a good functional food for diabetes intervention [ 14 ], but its potential as a remedy for diabetes has not been fully determined . The leaves of L. fischeri are another edible herb distributed throughout Eastern Asia including Korea, China, and Japan and are used as a traditional medicine for the treatment of inflammatory and infectious diseases, as well as obesity [ 26 , 27 ]. Here, we demonstrated the antidiabetic potential of LFE based on its ability to decrease blood glucose, TG, T-Chol, and NEFA levels in STZ/ATH mice ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a nonmedicinal alternative, MCE has been found to be a good functional food for diabetes intervention [ 14 ], but its potential as a remedy for diabetes has not been fully determined . The leaves of L. fischeri are another edible herb distributed throughout Eastern Asia including Korea, China, and Japan and are used as a traditional medicine for the treatment of inflammatory and infectious diseases, as well as obesity [ 26 , 27 ]. Here, we demonstrated the antidiabetic potential of LFE based on its ability to decrease blood glucose, TG, T-Chol, and NEFA levels in STZ/ATH mice ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt signaling pathway serves pivotal roles in the growth, migration and formation of blood vessels in endothelial cells ( 11 , 12 ). Our group has previously reported that the ethanolic extracts of Ligularia fischeri and Broussonetia kazinoki inhibited the proliferation, invasion and tube formation of endothelial cells by inactivation of the mitogen- and VEGF-A-stimulated signaling pathways, including the PI3K/Akt signaling pathway ( 37 , 38 ). To the best of our knowledge, the present study demonstrated for the first time that ETR inhibited mitogen-induced endothelial cell proliferation, adhesion, migration, invasion and tube formation.…”
Section: Discussionmentioning
confidence: 99%
“…(Compositae) has been used as a traditional medicine for the treatment of rheumatoid arthritis, scarlet fever and jaundice in eastern Asia including Korea, China and Japan. Previous investigations demonstrate that L. fischeri extract and its bioactive components such as caffeic acid and chlorogenic acid isomers possess anti-oxidant, anti-inflammatory, anti-angiogenic and anticancer properties (9)(10)(11). Chlorogenic acid isomers including 5-caffeoylquinic acid (5-CQA), which have been identified in a variety of plants including green coffee beans, walnut (Juglans regia L.) leaves, yerba-mate (Ilex paraguariensis) extract, Petasites japonicus extract and Marrubium vulgare extract as well as L. fischeri extract, have been known to exert a variety of biological functions such as anti-oxidant, anti-microbial, anti-diabetic, anti-inflammatory and anticancer activities (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%